A world class manufacturing model for South Africa - Muregerera, Herbert (Engineering Management, 2026)
The objective of this thesis is to develop a South African model for a world class manufacturing organisation. To achieve this a Cape Town based organisation, Omnigraphics, was analysed and used in the formulation of the concepts necessary for achieving the objective. The first three chapters form the major section of this thesis; they describe the development of the framework for managerial inquiry and learning. The development of the framework outlines three levels crucial for understanding and effectively managing organisations. These levels are: the philosophical level, the methodology level, and the implementation or action level. The philosophical level looks at the fundamental assumptions about the world or, rather, how people make sense of the world. Organisational cultural changes, for example, take place at the philosophical level of consideration. Charles Sanders Peirce's philosophy of fixing belief was appropriately chosen as the philosophy that best suits the managerial inquiry requirements of today. All methodologies derive from some philosophy and all actions are based on some corresponding methodology. The methodology of this thesis is based on the Scientific Method as described, separately, by Revans and Peirce. The development of the methodology analyses four methods of fixing belief and finally settles for the method of science as the most suitable because of its self verification characteristics. The method of science, as described by Revans and Peirce, is weighed against the learning cycles of Handy and Kolb, as well as Ryan's framework. From the synthesis of these works emerged a framework for managerial inquiry and learning. The framework was used to inquire into the operational situation of Omnigraphics in view of it being considered for world class manufacturing status. The tools of Soft Systems Methodologies and Multiple Perspectives methods, as incorporated in the framework developed, were used to objectively inquiring into the organisation. The issues of concern that arose were those of cultural change conflict, production processes inconsistencies and quality-related problems, lack of definite strategy and/ or vision, and communication across and within the hierarchical levels. The dominant single concern, though, was the 'we-they' split between the workers and management. These issues were explored in selected literature appropriate for the conditions that are currently prevailing at Omnigraphics. The chapter on organisational culture outlined the behavioural aspects of an organisation and how "the way we do things around here" can be changed. Within the organisational culture are embedded the beliefs and assumptions that define the learning systems which characterise the organisation. The people in the organisation shape the culture in the way they interact in their day-to-day activities at work. Thus, the 'we-they' situation was seen as a culture that needed change because it prohibits effective learning and, therefore, stifles continuous improvement necessary for world class manufacturing. The Work Systems Framework (WSF), as described by Luc Hoebeke (1994), was found to be suitable for the world class manufacturing concerns discussed. The WSF was built around the aspects of statistical process control, quality function deployment and benchmarking. These aspects were carefully selected and incorporated, and described in their nature as enhancing organisational change through learning. The organisational learning processes are described as taking place at two levels: within the organisation and within the environment that the organisation serves. The information strengths of cybernetics are used to describe the learning environment. The 'new' process-based structure is shown to be adaptive by virtue of its learning-driven nature which facilitates world class manufacturing. Learning is demonstrated as taking place at all levels of the organisation. This led in the analysis of worker empowerment as facilitating learning at the lowest level of the organisation. Coupled with this is the new concept of Workplace forums as illustrated in the new South African Labour Relations Bill of 1995. The concepts of these Workplace forums are tied in with those of worker empowerment as a revolt against Taylorism. Various real organisational cases were used to test the validity of the WSF model developed. The results of these tests confirmed the validity of the concepts outlined. Of notable significance are the intertwined relationships existing amongst the concepts of organisational learning, cultural change and sustainable competitive advantage. The organisational culture describes the behavioural aspects of the organisation as well as those of its people as determined by experiences acquired over time. The work that brought about this thesis was confined to the operational processes that define a successful world class organisation. Aspects of organisational structure were not considered. Finer psychological aspects of worker motivation, team building and job satisfaction were outside the scope of the thesis.